Downriver : into the future of water in the West - Hansman, Heather (The University of Chicago Press, 2019)
The Green River, the most significant tributary of the Colorado River, runs 730 miles from the glaciers of Wyoming to the desert canyons of Utah. Over its course it meanders through ranches, cities, national parks, endangered fish habitats, and some of the most significant natural gas fields in the country, as it provides water for 33 million people. Stopped up by dams, slaked off by irrigation, and dried up by cities, the Green is crucial, overused, and at risk, now more than ever. Fights over the river<U+2019>s water, and what<U+2019>s going to happen to it in the future, are longstanding, intractable, and only getting worse as the West gets hotter and drier and more people depend on the river with each passing year. As a former raft guide and an environmental reporter, Heather Hansman knew these fights were happening, but she felt driven to see them from a different perspective<U+2014>from the river itself. So she set out on a journey, in a one-person inflatable pack raft, to paddle the river from source to confluence and see what the experience might teach her. Mixing lyrical accounts of quiet paddling through breathtaking beauty with nights spent camping solo and lively discussions with farmers, city officials, and other people met along the way, Downriver is the story of that journey, a foray into the present<U+2014>and future<U+2014>of water in the West.